Who makes the rules of globalization? - Alan V. Deardorff (Center for Economic Studies and ifo Institute (CESifo), 2004)
In this paper I argue that profit-maximizing firms, even though they contribute to social welfare when they compete in the market, may not do so when they influence the political process. In particular, I suggest, through several examples from both the real world and from economic theory, that corporations have played a significant role in the formulation of the rules of the international trading system. They did this in the formation of the WTO, where they were responsible for the expansion to cover both intellectual property and services. And they do this in preferential trading arrangements such as the NAFTA, where they inserted the notorious Chapter 11 and specified rules of origin for automotive products. All of this is quite consistent with economic theory, including the literature on the political economy of trade policy. I also use a simple duopoly model to illustrate a domestic firm's interest in setting rules of origin. The corporate influence on rules need not be bad, but there is no reason why it should be good either, as these examples illustrate.
Keywords: F13; 330; political economy of trade; trade institutions; Internationale Wirtschaftsorganisation; Public Choice; Interessenpolitik; Duopol; World Trade Organization; North American Free Trade Agreement